Assessment of Safety and Health Risks of Seismic Projects by HAZAN Method - Arsalan Arsalan RAZMJOEI; Leila Ebrahimi Ghavam Abadi; Amin Delavar; Hamideza Pakbaz (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: The oil and gas industries are considered as the most important industries in Iran, where a significant part of the budget depends on these two areas The significant health and safety implications of these industries on the staff and stakeholders have also been highlighted. Methods: The present study was conducted to identify and assess the safety and health risks of the Fars Mountain Seismology project using HAZAN method in 2016 and 2017.  The hierarchical task analysis  (HTA) was used to analyze the main tasks of the main occupations: digger, surveyor, shooter, drivers, and helicopter pilot . The risk assessment process identified in the HAZAN method was based on the qualitative matrix.  In HAZAN, 50 health and safety risks were identified. Results: The results showed that eight risk factors (16%) were unacceptable, 25 were unsatisfactory (50%) and 17 (34%) were acceptable. Conclusion: The results showed that the aviation and land transport processes as well as the traffic on mountain routes were the most expensive activities in the project.  Finally, management solutions were proposed to reduce the risk level related to the most important project activities